Structured Region Graphs: Morphing EP into GBP - Welling, Max; Minka, Tom; Teh, Yee Whye (UAI, 2005)
GBP and EP are two successful algorithms for approximate probabilistic inference, which are based on different approximation strategies. An open problem in both algorithms has been how to choose an appropriate approximation structure. We introduce “structured region graphs,” a formalism which marries these two strategies, reveals a deep connection between them, and suggests how to choose good approximation structures. In this formalism, each region has an internal structure which defines an exponential family, whose sufficient statistics must be matched by the parent region.